2020
DOI: 10.1002/path.5555
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the SARS‐CoV‐2 receptor ACE2 is induced by cigarette smoke in bronchial and alveolar epithelia

Abstract: Angiotensin‐converting enzyme 2 (ACE2) has been identified as the functional receptor of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and a target for disease prevention. However, the relationship between ACE2 expression and its clinical implications in SARS‐CoV‐2 pathogenesis remain unknown. Here, we explored the location and expression of ACE2, and its correlation with gender, age and cigarette smoke (CS), in a CS‐exposed mouse model and 224 non‐malignant lung tissues (125 non‐smokers, 81 cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 54 publications
2
62
0
1
Order By: Relevance
“…Moreover, hypoxia reduced the infection rate of Vero E6 cells by pseudotyped SARS-CoV-2 lentiviral particles. The observed reduction of ACE2 protein level contrasts with the early transcriptional increase of this gene, a well-documented observation that likely results from the binding of the hypoxia inducible factor (HIF) transcription factors to hypoxia response elements on the ACE2 promoter (Liu et al, 2020). The observed discrepancy at the RNA vs. protein ACE2 levels might be explained by protein degradation, cleavage (Heurich et al, 2014) or timedependent adaptation to hypoxia.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, hypoxia reduced the infection rate of Vero E6 cells by pseudotyped SARS-CoV-2 lentiviral particles. The observed reduction of ACE2 protein level contrasts with the early transcriptional increase of this gene, a well-documented observation that likely results from the binding of the hypoxia inducible factor (HIF) transcription factors to hypoxia response elements on the ACE2 promoter (Liu et al, 2020). The observed discrepancy at the RNA vs. protein ACE2 levels might be explained by protein degradation, cleavage (Heurich et al, 2014) or timedependent adaptation to hypoxia.…”
Section: Discussionmentioning
confidence: 88%
“…This result differs from significant ACE2 upregulation reported by Liu et al . in human lung specimens of cigarette smokers and may be explained by the relative lack of chronicity in the NHP model [ 44 ]. However, consistent with our findings, images of human airways from non-smokers in the paper by Liu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological investigations proposed a potential relationship between PM2.5 concentrations and the susceptibility severity of SARS-CoV-2 [ 31 , 32 , 33 , 34 ], which might be closely associated with altered expression of ACE2 by chronic exposure to fine PM2.5 [ 35 ]. Recently, computational analysis of sequencing data from patients with chronic lung diseases revealed that dysregulation of androgen, hypoxia-inducible factor 1-alpha, interferon, and IL-6 cytokine pathways is associated with upregulation of ACE2 and SARS-Cov-2 severity [ 36 , 37 , 38 , 39 , 40 ]. To the best of our knowledge, this is the first study reporting the transcriptional and translational upregulation of ACE2 in hPSC-derived AECs and 3D AOs by exposure to dPM2.5.…”
Section: Discussionmentioning
confidence: 99%